Feasibility of a CMM telepharmacy service for patients with diabetes in rural and underserved communities: Preliminary results. Issue 8 (19th July 2021) - Livet, Melanie; Levitt, Jordana; Cardenas, Amy; Thomas, Jeremy; Lee, Alyssa; Pathak, Shweta; Curran, Geoffrey
Abstract: Introduction: Patients with uncontrolled diabetes living in rural and underserved communities experience many challenges, including lack of access to needed health and medication management services. Telepharmacy has been identified as a promising approach for addressing this gap. This article describes early insights into the implementation and effectiveness of a comprehensive medication management (CMM) telepharmacy service offered as part of primary care clinics in North Carolina and Arkansas. The CMM service involved pharmacists meeting remotely with patients in their homes to identify and resolve medication‐related problems (MTPs). Objectives: The purpose of this article is to both describe early successes, challenges, and lessons learned, and summarize preliminary effectiveness results. Methods: This exploratory study made use of mixed methods data spanning the first three months of implementation. Successes, challenges, and lessons learned were captured through clinic interviews, open‐ended survey questions, and pharmacists' logs. Evidence of implementation progress and success was based on administrative data and implementation outcomes survey results. Medication therapy problems (MTPs) were used as a proxy to assess preliminary service effectiveness. Results: Key insights centered on the perceived benefits of the service for patients and clinics, the importance of patient outreach and engagement, access to implementation support strategies, and the need for adaptability. Implementation success was rated highly by clinic stakeholders, with significant increases in service acceptability, appropriateness, and feasibility over time, and continued intent to maintain the service. The MTP resolution rate averaged 88% across pharmacists. Conclusion: These preliminary data are promising for supporting the value of a pharmacist‐led medication optimization service delivered remotely to complex patients with uncontrolled diabetes. Ultimately, this model has the potential to expand access to care and transform the delivery of pharmacy services, while creating an opportunity to evolve the role of the clinical pharmacist beyond the traditional boundaries.